IMPLEMENTASI FULL DAY SCHOOL (SEKOLAH SEHARI PENUH) SEBAGAI BEST PRACTICE (LATIHAN TERBAIK) DALAM PENDIDIKAN KARAKTER DI SMA NEGERI 1 SRAGEN - Sari, Prima Ratna; Wardani, Dewi Kusuma; Noviani, Leny (Department of Economics Education, Universitas Sebelas Maret, 2017)
The research is aimed to discover the implementation, the level of successfulness and the obstacles during the full day school implementation at characters education.Phenomenology method is used in the research with the approach of qualitative research. The sources of the data are primary and secondary data. Technique are used in the research are planned unstructured interview, observation and documentation. The sampling techniques are used purposive sampling and snowball sampling. Credibility test and dependability test are used to test the validity of the data with the analysis technique data before and after of the field. There are three stages of analysis in the field; data reduction, data display and data summary.The finding of the research are as follows: first, characters education through the implementation of full day school implemented by three basic steps from the guidance of characters education strengthening (PPK), such as PPK in the class basic, PPK with school’s culture basic and PPK with community’s basic. Activities at PPK’s class basic consist of integration in learning subjects, the optimization of local wisdom, class management and PPK in the form of guidance and counselling services. Activities at PPK with school’s culture basic consist of habitual of school’s values in the daily life at school, educators’ role-modelling, school’s environment, school’s rules, and the developing of co-curricular and extra-curricular activities. Activities at PPK with community’s basic still in the form of involvement of parents and school’s committee. Second, the successfulness of characters education through the implementation of full day school shown by the embedding of five main values of the character based on the Basic Concept of PPK Kemendikbud 2016. Third, the factors which becomes the obstacles to implement the characters education through full day school are lack of time, energy, and mind that caused the fatigue and unable to manage the time. Full day schools also have economic links to students.